2016
DOI: 10.1139/cjas-2016-0055
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with serum vitamin A and E concentrations in beef calves from Alberta and Saskatchewan and the relationship between vitamin concentrations and calf health outcomes

Abstract: The study objectives were to identify factors associated with serum vitamin A and vitamin E concentrations in beef calves less than 1 mo old and to examine associations between vitamin concentrations and health outcomes. Serum vitamin A concentrations were highest in calves more than 4 d old, with serum immunoglobulin G concentrations > 19 g L −1 , from cows without perinatal health problems, and born where precipitation in the previous growing season was ≥200 mm. Serum vitamin E was highest in calves more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 45 publications
8
80
5
4
Order By: Relevance
“…Other studies have shown relatively similar serum IgG concentrations for beef (Waldner and Rosengren 2009) and dairy calves (Deelen et al 2014). However, in the present study, there was no difference between colostrum IgG and breed of cow; this was in agreement with findings from Murphy et al (2005), who observed cow breed to have no significant effect on colostral IgG1 concentration between five suckler cow breed types.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have shown relatively similar serum IgG concentrations for beef (Waldner and Rosengren 2009) and dairy calves (Deelen et al 2014). However, in the present study, there was no difference between colostrum IgG and breed of cow; this was in agreement with findings from Murphy et al (2005), who observed cow breed to have no significant effect on colostral IgG1 concentration between five suckler cow breed types.…”
Section: Discussionsupporting
confidence: 93%
“…In Table 2, more variation was observed in corti sol levels in the current study than in previous research (7.00 to 29.50 ng/mL; Bristow and Holmes, 2007). Immunoglobulin G and isotype levels were lower in these steers than in beef calves from previous research (Waldner and Rosengren, 2009). Similar to our find ings, Kimura et al (2002) determined plasma IL8 lev els in dairy cattle with retained placentas ranged from 134 to 300 pg/mL.…”
Section: Applicability Of Results To Us Beef Industrycontrasting
confidence: 46%
“…Although that cheap indirect screening tests, such as determination of total protein (TP) with a refractometer, perform reasonably well, direct determination of immunoglobulins (Ig) or IgG is generally more specific (Weaver et al, 2000). In calves sampled within a week after birth a cut off value for IgG of 10 g/L is generally accepted to determine FPT, and has been linked with disease occurrence, although some studies reported higher cut-offs in particular situations (Waldner and Rosengren, 2009;Furman-Fratczak et al, 2011;Stilwell and Carvalho, 2011). In contrast, it is currently unknown whether Ig levels measured at the age of arrival in veal calves (2-4 weeks old) can be used as predictors of BRD or NCD.…”
Section: Introductionmentioning
confidence: 99%